Drug interactions in HIV patients treated in a high complexity hospital of Antofagasta city - Patricio R. Araya; Criss V. Zambra; Yoselyn M. Castillo; Pedro P. Usedo; Francisco L. Salvador; Francisco J. González (GarVal Editorial Ltda., 2017)
Context: From the beginning of the global HIV epidemic there has been a great concern about drug interactions (DI) considering that up to 27% of all patients may be affected by at least one type of DI, this risk increases by receiving concomitant treatments. This DI leads to negative consequences such as adverse drug reactions (ADR), lack of treatment adherence and new hospital admissions. Aims: To determine the prevalence of DI of antiretroviral drugs and their clinical consequences in UNACESS-VIH-SIDA patients of Hospital Regional de Antofagasta. Methods: The study included a total of 100 HIV patients. To identify DI, Micromedex database was used. All data were gathered in a pharmaceutical datasheet, the theoretical DI were identified and real DI were detected by using hematologic tests and the patient's clinical evolution. After the detection of any real DI, a pharmaceutical intervention took place. Results: A total of 106 DI were detected; 86% of DI found were related to drug's pharmacokinetic properties, which were mostly metabolism related interactions (96.9%); the most commonly found associations were atazanavir with ritonavir, efavirenz with atorvastatin and efavirenz with gemfibrozil. The main clinical consequences associated with DI were ADR (49%). Conclusions: High prevalence of metabolism-related interactions was found and the antiretroviral drugs mostly associated with DI were found to be atazanavir, ritonavir y efavirenz. A high prevalence of ADR was found; however, they were mild or moderate.